(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Marketing came into Indian banks in the late 1950’s not in the form of marketing concept but in the forms ofadvertising and promotion concept. Soon it was realised that marketing transcendsadvertising and friendliness. Till 1950 it was recognised that personal sellingwas not necessaiy. The bankers went out of their way to avoid being accused ofselling. The bankers even eliminated the word ’selling’ and they called thefunction of customer contact ’business development function.